Numerological phraseological units in the Kazakh and Chinese - Dosymbekova, R. O. (Journal of Oriental Studies, 2016)
This article discusses the formation of numerology in China on the basis of research scientists. Also considered numerological phraseological One unit in the Kazakh and Chinese.